Overexpression of Glycogen Synthase Kinase-3 in Ovarian Carcinoma Cells With Acquired Paclitaxel Resistance. Issue 3 (1st April 2011) - Fu, Yunfeng; Hu, Dongxiao; Qiu, Jian; Xie, Xing; Ye, Feng; Lu, Wei-Guo
Abstract : Introduction: Acquired resistance to paclitaxel, including regimens, is one of the most significant reasons for treatment failure and death in patients with ovarian cancer, but the causes of this resistance remain unclear. However, cell cycle regulation is a key mechanism by which most chemotherapeutic agents exert their cytotoxic effects. Methods: We created a paclitaxel-resistant ovarian carcinoma cell line from SKOV3 cell line, and the difference of cell cycle distribution was analyzed using flow cytometry. Analysis of human cell cycle pathway complementary DNA array was performed to identify candidate genes associated with paclitaxel resistance. Gene expression changes were validated at the messenger RNA and protein levels by real-time reverse transcriptase polymerase chain reaction and Western analysis, respectively. Results: The ratio of Gap0 /Gap1 phase in SKOV3-TR30 was significantly lower than that in SKOV3 (54.8% ± 6.3% vs 72.7% ± 7.6%, P = 0.035), and the ratio of G2 /M phase in SKOV3-TR30 was significantly higher than that in SKOV3 (24.9% ± 6.0% vs 10.2% ± 3.5%, P = 0.021). Complementary DNA microarray analysis demonstrated enhanced glycogen synthase kinase-3α (GSK-3α) expression in paclitaxel-resistant ovarian carcinoma cells. Real-time reverse transcriptase polymerase chain reaction analysis revealed that the paclitaxel-resistant subline exhibited a 7.0 ± 1.8-fold increase in GSK-3α messenger RNA expression. There was a 3.34 ± 0.47-fold increase of total GSK-3 protein (GSK-3α/β) in SKOV3-TR30 cells validated by Western analysis. Conclusions: This study demonstrates that enhanced expression of GSK-3 is associated with acquired resistance to paclitaxel in ovarian carcinoma cells. Glycogen synthase kinase-3 overexpression may probably be a significant contributor to chemoresistance.